EFFORTS TO IMPROVE COMMUNITY LITERACY THROUGH THE PORT NUMBAY READING CORNER PROGRAM IN FANAMO VILLAGE, EASTERN MIMIKA DISTRICT, MIMIKA REGENCY, PAPUA PROVINCE - Farawowan, Fauziah F; Hartati, Yuniar Sri; Mas'ud, Marwah; Lerebulan, Mey Mony; Golam, Mohamad Yusuf (TOPLAMA, 2024)
This study aims to evaluate the impact of the Pojok Baca program in Kampung Fanamo on improving community literacy, particularly among children and teenagers. The research method used includes the establishment of Pojok Baca as a literacy center, training for managers and the community, and the integration of technology to expand access to information. Data were collected from various sources, including visitors to Pojok Baca, teachers, and local community leaders, to obtain a comprehensive overview of the program's effectiveness. The results indicate that the Pojok Baca program successfully achieved its primary objectives of increasing reading interest and literacy skills within the community. The increase in the number of visitors and book borrowings, as well as reports from local teachers, show significant improvements in the reading and writing skills of children involved in this program. Additionally, the formation of an active literacy community indicates that the program has also successfully encouraged social engagement and collaboration among residents. Although the program faced several challenges, such as limited infrastructure and logistics, the participatory approach involving the community in every stage of the program's implementation proved effective in overcoming these obstacles. In conclusion, this study demonstrates that with appropriate support and a participatory approach, literacy programs like Pojok Baca can have a significant positive impact on improving literacy in remote areas and empowering communities to actively participate in social change.